Effect of sodium silicate concentration on the physico-chemical properties of dual-setting bone-like apatite cements. (June 2022) - Lakrat, Mohammed; Mejdoubi, El Miloud; Ozdemir, Fatma; Santos, Catarina
Abstract: Calcium phosphate cements (CPCs) with their biocompatibility, osteoconductivity and injectability plays an important role in bone defects treatment. Dual-setting cement is a promising approach to improve the physicochemical and biological properties of CPCs in which the liquid phase contains dissolved monomers that polymerized during hardening process. In this study, a series of dual-setting cements were prepared by mixing dicalcium phosphate dihydrate (DCPD) as a solid phase and sodium silicate solution (SS) with different concentrations as hardening liquids. The idea was to evaluate the effect of SS concentration on the setting mechanism, physicochemical and mechanical properties of the formulated cements. The setting kinetics was attributed to the DCPD dissolution and calcium deficient hydroxyapatite (CDHA) precipitation in parallel to SS polymerization to form sodium silicate gel. This was responsible for the formation of an interpenetrating composite material in which the formed gel fills the micropores of the CPC cement. The results showed that the setting time can be modulated by varying the SS concentrates in the hardening liquid. It was shown, as the SS content in the cement liquid increased from 10 to 30 wt%, the setting time decreased from 56 to 5 min. Moreover, the DCPD dissolution and CDHA precipitation were accelerated by increasing the SS concentration. The bone-like apatite cement with the highest SS content exhibited an enhanced compressive strength and high resorption rates. Overall, the addition of sodium silicate gel is a promising approach to regulate the different properties of the apatite-forming cement to be used for bone fracture treatment. Graphical Abstract: ga1